COMPARISON OF THE SELECTED MOTION INTERPOLATION METHODS - Skublewska-Paszkowska, Maria; Smołka, Jakub (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
Interpolation is one of key aspects of computer animation. The selection of the proper interpolation method influences motion of animated objects. The paper presents selected interpolation methods and compares them with respect to computation time and accuracy. The three algorithms that were analyzed are: Catmull-Rom Spline, modified Catmull-Rom Spline and Blended Parabolas method. Numerical experiments were performed using a program written in C++ language.